Pemberian Saran Untuk Mencari Kosakata Menggunakan Algoritma Brute Force Dan Steganografi - Indra Gunawan; Sumarno Sumarno; Heru Satria Tambunan; Abdi Rahim Damanik (Teknik Komputer Politeknik Negeri Sriwijaya, 2021)
Searching data in the computer system by using the data search tool can make it easier for users to search for data and information. In order to make it easier for users to search for data and information, it is necessary to modify and implement several algorithms or methods to provide additional features by providing vocabulary suggestions by matching strings that can be an alternative to the search for data and information. Brute force algorithm has a way of performing string searches by randomly searching from each string to find a matching string and which will be used to perform a data search, while the steganography algorithm has a way of working to insert objects, be it in the form of characters or images. Combining the two algorithms and combining each of its performance advantages, so as to provide suggestions in the process of searching for data and information through data search. The result is brute force algorithm will search the data by shifting from each string, so in doing the data search will take a short time while the steganography algorithm performs the storage of data that has been done matching in the process of searching for data that aims to search the next data.